KERAGAMAN PRODUK, PROMOSI DAN HARGA PRODUK TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA TOKO OFFICIAL KOPI KOPRAL DI SITUBONDO - Samuel Umbu Warata; Nanda Widaninggar; Ayu Dita Windra Ciptasari (Fakultas Ekonomi dan Bisnis, 2025)
In the increasingly competitive situation in Indonesia, it encourages increasing consumer expectations towards various aspects. Businesses that want to survive and grow must be able to meet these expectations by innovating and providing the best service to consumers. Competition in the retail sector today is not only focused on price but also involves various other variables related to the consumer shopping experience. The use of the internet opens up various business opportunities that can be run by the community. With this technology, the interaction between consumers and sellers becomes easier, because consumers can shop without having to meet the seller directly. On the other hand, sellers can also market their products or services more effectively through various digital platforms. Marketing is not just about promotion or sales, but also includes various strategies to create value for customers and build long-term profitable relationships, so there are variables that can influence it, namely: Product Diversity Promotion Price on Customer Loyalty and Consumer Satisfaction. Analysis and hypothesis testing in this study used the Partial Least Square Structure Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 Application, Product Diversity has a significant positive effect on Customer Satisfaction. Promotion has a significant positive effect on Customer Satisfaction. Product Price has a negative but insignificant effect on Customer Satisfaction. Product Diversity has a significant positive effect on Customer Loyalty. Promotion has a negative but insignificant effect on Customer Loyalty Customer Price has a negative but insignificant effect on Customer Loyalty. Customer Satisfaction has a negative but insignificant effect on Customer Loyalty. Product Diversity has a negative but insignificant effect on Customer Loyalty through Customer Satisfaction. Promotion has a negative but insignificant effect on Customer Loyalty through Customer Satisfaction. Price has a negative but insignificant effect on Customer Loyalty through Customer Satisfaction.